Utility of Multi-target Nested PCR and ELISPOT Assays for the Detection of Paucibacillary Leprosy: A Possible Conclusion of Clinical Laboratory Misdiagnosis - Jiang, Haiqin; Shi, Ying; Chokkakula, Santosh; Zhang, Wenyue; Long, Siyu; Wang, Zhenzhen; Kong, Wenming; Long, Heng; Wu, Limei; Hu, Lihua; Yao, Qiang; Wang, Hongsheng (Frontiers in Cellular and Infection Microbiology, 2022)
The diagnosis of paucibacillary (PB) leprosy often pose diagnostic challenges, especially for pure neuritis and lesser skin lesions with the zero bacillary load, requiring a sensitive and accurate diagnostic tool. We have included 300 suspected leprosy cases (comprising 98 PB patients) and analysed sensitivity and specificity of PB leprosy cases were obtained by nested PCR with FolP, GyrA, RpoB, RLEP and 16SrRNA and Enzyme-linked Immunospot Assay test (ELISPOT) with MMPII, NDO-BSA and LID-1 antigens by detecting IFN-γ release. The overall positivity rate of genes tested in 300 suspected leprosy cases were identified as 55% of 16SrRNA, 59% of RLEP, 59.3% of FolP, 57.3% of RpoB, 61% of GyrA, while 90% of nested FolP, 92.6% of nested RpoB, 95% of nested GyrA and at least one gene positive cases were 285 (95%). For PB cases, 95% PCR positivity was achieved by three tested genes in nested PCR. The data obtained from ELISPOT for three antigens were analyzed IFN-γ expression with 600 subjects. Among 98 suspected PB leprosy specimens, the sensitivity of MMP II, LID-1 and NDO-BSA was 90%, 87% and 83%, and the specificity was 90%, 91% and 86% respectively. Total number of specimens positive for at least one antigen was 90 (91.8%) in PB significantly higher than multibacillary (MB) suspected leprosy (56.7%). The combination of muilt-targets nested PCR and ELISPOT assay provides a specific tool to early clinical laboratory diagnosis of suspected PB leprosy cases. The two assays are complementary to each other and beneficial for screening PB patients.